2010
DOI: 10.1063/1.3506499
|View full text |Cite
|
Sign up to set email alerts
|

Position controlled nanowires for infrared single photon emission

Abstract: We report the experimental demonstration of single-photon and cascaded photon pair emission in the infrared, originating from a single InAsP quantum dot embedded in a standing InP nanowire. A regular array of nanowires is fabricated by epitaxial growth on an electron-beam patterned substrate. Photoluminescence spectra taken on single quantum dots show narrow emission lines. Superconducting single photon detectors, which have a higher sensitivity than avalanche photodiodes in the infrared, enable us to measure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
49
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(51 citation statements)
references
References 17 publications
2
49
0
Order By: Relevance
“…2(d)], which suggests that the investigated InAsP QD exhibits a type I transition and thus a zinc-blende-like crystal structure. These observed results and the quantum-disk-like structure (height, ∼9 nm; diameter, ∼100 nm) 19 indicate that the X 0 initial state is localized in a type I confinement potential as well as a relatively weak lateral confinement of the InAsP QD embedded in the InP NW. In what follows we focus on X 0 , which generates the single-photon state estimated by the second-order photon correlation measurements presented in Ref.…”
Section: Sample Preparation and Measurement Setupmentioning
confidence: 58%
See 1 more Smart Citation
“…2(d)], which suggests that the investigated InAsP QD exhibits a type I transition and thus a zinc-blende-like crystal structure. These observed results and the quantum-disk-like structure (height, ∼9 nm; diameter, ∼100 nm) 19 indicate that the X 0 initial state is localized in a type I confinement potential as well as a relatively weak lateral confinement of the InAsP QD embedded in the InP NW. In what follows we focus on X 0 , which generates the single-photon state estimated by the second-order photon correlation measurements presented in Ref.…”
Section: Sample Preparation and Measurement Setupmentioning
confidence: 58%
“…In what follows we focus on X 0 , which generates the single-photon state estimated by the second-order photon correlation measurements presented in Ref. 19.…”
Section: Sample Preparation and Measurement Setupmentioning
confidence: 99%
“…There have been many studies of heterostructure QD NW, mostly concerning InAs/ GaAs and InAs/InAsP QD NWs. [19][20][21][22][23][24] Of these studies, two reports show that a photonic NW can control the spontaneous emission. 22,24 They found that the spontaneous emission was greatly inhibited (between 12-and 16-fold) for a smallfacet NW (sl < 100 nm), from which they determined that the quantum efficiency of the QD NW was between 92% and 97%.…”
Section: Light-matter Interaction Of the Embedded Emitter Nwmentioning
confidence: 98%
“…[5][6][7][8] Among them, InGaAs NWs are a very promising for various applications because of their high electron mobility and good interface properties. 6,[9][10][11][12] These properties as well as the bandgap energy can be controlled by adjusting the alloy composition of InGaAs.…”
mentioning
confidence: 99%